Influence of Concrete Compressive Strength on L-Shaped Shear Wall Performance in Buildings within High-Seismicity Zones - Salem Merabti; Layachi Guelmine (The Journal of Engineering and Exact Sciences)
Reinforced concrete mid-rise structures are supported by shear walls to withstand lateral forces resulting from earthquakes. In this context, the presence of openings in these walls is essential both functionally and aesthetically. This study employed L-shaped shear walls with varying vertical opening ratios, ranging from 15% to 50%, and compressive strengths ranging from 20MPa to 40MPa in a ten-story building. The study results demonstrate the significant role played by openings and the compressive strength of concrete in reinforced concrete walls to ensure buildings withstand earthquake forces. In this regard, we have developed reference models that adhere to seismic design principles and utilize optimized dimensions for openings based on the compressive strength of the concrete.